Companies, Code, and Coordination: An Actor-Network Analysis of OSS 2.0 (Syracuse University School of Information Studies, 2021)
Open source software is increasingly driven by a combination of independent and professional developers, the former volunteers and the later hired by a software company to contribute to the project to support commercial product development. This mix of developers has been referred to as OSS 2.0. However, we do not fully understand the coordination spanning individuals, teams, and organizations in OSS 2.0. Using Actor-Network Theory (ANT), we describe how coordination and power dynamics unfold and how technological artifacts both display actions and mediate coordination efforts. Internal coordination within an organization was reported to create competing networks against the network for the whole OSS community by breaking the alignments of interests. ANT shows how software development tools and code, as active actors, exercise agency in attracting developers to work on problems and informing the layers of collaboration. We discuss the theoretical and practical implications of the changing nature of OSS.